Role of bone morphogenetic proteins in sprouting angiogenesis: differential BMP receptor‐dependent signaling pathways balance stalk vs. tip cell competence. Issue 11 (21st July 2017) - Benn, Andreas; Hiepen, Christian; Osterland, Marc; Schütte, Christof; Zwijsen, An; Knaus, Petra
Abstract : Before the onset of sprouting angiogenesis, the endothelium is prepatterned for the positioning of tip and stalk cells. Both cell identities are not static, as endothelial cells (ECs) constantly compete for the tip cell position in a dynamic fashion. Here, we show that both bone morphogenetic protein 2 (BMP2) and BMP6 are proangiogenic in vitro and ex vivo and that the BMP type I receptors, activin receptor‐like kinase 3 (ALK3) and ALK2, play crucial and distinct roles in this process. BMP2 activates the expression of tip cell–associated genes, such as delta‐like ligand 4 ( DLL4 ) and kinase insert domain receptor ( KDR ), and p38‐heat shock protein 27 (HSP27)–dependent cell migration, thereby generating tip cell competence. Whereas BMP6 also triggers collective cell migration via the p38‐HSP27 signaling axis, BMP6 induces in addition SMAD1/5 signaling, thereby promoting the expression of stalk cell–associated genes, such as hairy and enhancer of split 1 ( HES1 ) and fms‐like tyrosine kinase 1 ( FLT1 ). Specifically, ALK3 is required for sprouting from HUVEC spheroids, whereas ALK2 represses sprout formation. We demonstrate that expression levels and respective complex formation of BMP type I receptors in ECs determine stalk vs . tip cell identity, thus contributing to endothelial plasticity during sprouting angiogenesis. As antiangiogenic monotherapies that target the VEGF or ALK1 pathways have not fulfilled efficacy objectives in clinical trials, the selective targeting of the ALK2/3 pathways may be an attractive new approach.—Benn, A., Hiepen, C., Osterland, M., Schütte, C., Zwijsen, A., Knaus, P. Role of bone morphogenetic proteins in sprouting angiogenesis: differential BMP receptor‐dependent signaling pathways balance stalk vs . tip cell competence. FASEB J. 31, 4720–4733 (2017). www.fasebj.org